2021
DOI: 10.3390/ijms22052602
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Select Dietary Emulsifiers Exacerbates the Development of Spontaneous Intestinal Adenoma

Abstract: Inflammation is a well-characterized critical driver of gastrointestinal cancers. Previous findings have shown that intestinal low-grade inflammation can be promoted by the consumption of select dietary emulsifiers, ubiquitous component of processed foods which alter the composition and function of the gut microbiota. Using a model of colitis-associated cancer, we previously reported that consumption of the dietary emulsifiers carboxymethylcellulose or polysorbate-80 exacerbated colonic tumor development. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Carboxymethylcellulose (CMC) and polysorbate 80 (P80) are some of the most commonly used emulsifiers, a subtype of food additives. Their regular consumption showed to exacerbate colorectal tumor development in a preclinical model of colitis-induced colorectal cancer [ 215 ], and to aggravate the initiation and development of genetically driven CRC, as demonstrated in mice mutated for the tumor suppressor gene APC [ 216 ]. In this study, the LINE-1 methylation status on formalin-fixed, paraffin-embedded samples of neoplastic colonic mucosa as well as microbiota on stool samples of eoCRC patients could be evaluated in relation to dietary and lifestyle habits, also taking into account the new “age continuum” model proposed by Akimoto et al for this epigenetic alteration as compared to the sharp distinction between eoCRC and loCRC with the age cut-off set at 50 years [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carboxymethylcellulose (CMC) and polysorbate 80 (P80) are some of the most commonly used emulsifiers, a subtype of food additives. Their regular consumption showed to exacerbate colorectal tumor development in a preclinical model of colitis-induced colorectal cancer [ 215 ], and to aggravate the initiation and development of genetically driven CRC, as demonstrated in mice mutated for the tumor suppressor gene APC [ 216 ]. In this study, the LINE-1 methylation status on formalin-fixed, paraffin-embedded samples of neoplastic colonic mucosa as well as microbiota on stool samples of eoCRC patients could be evaluated in relation to dietary and lifestyle habits, also taking into account the new “age continuum” model proposed by Akimoto et al for this epigenetic alteration as compared to the sharp distinction between eoCRC and loCRC with the age cut-off set at 50 years [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…APC min mice – which are predisposed to intestinal adenoma formation – showed an increased number of adenomas in the small intestine, but not in the colon when fed a diet containing carboxy methyl cellulose (Viennois and Chassaing, 2021 ). Mutations in the APC gene are known to lead to adenomas and later, carcinomas, in the colon in humans (Markowitz and Bertagnolli, 2009 ).…”
Section: Assessmentmentioning
confidence: 99%
“…The Panel was made aware of recent studies in which sodium carboxy methyl cellulose was investigated in mice and humans. These studies addressing the microbiota and a few toxicological endpoints showed changes in the microbiota composition in mice and also in humans (Arnold et al, 2022;Chassaing et al, 2022;Chassaing et al, 2015;Naimi et al, 2021;Sandall et al, 2020;Viennois et al, 2020;Viennois and Chassaing, 2021). However, the consequences and the meaning of these changes in the microbiota composition for relevant health outcomes are currently not clear.…”
Section: Other Studiesmentioning
confidence: 99%
“…This along with unhealthy dietary habits, obesity, heme iron, and associated alterations in gut microbiota enhance oncogenic changes in colonic mucosa ( 68 ). Viennois et al reported that consumption of dietary emulsifiers such as carboxymethylcellulose (CMC) and polysorbate 80 (P80) alter the composition of the gut microbiome and increase the risk for intestinal inflammation and adenoma formation in Apc min mice ( 69 ). Emulsifier consumption lowered the abundance of Clostridia (in both male and female mice) and increased the abundance of Proteobacteria (in male mice).…”
Section: The Influence Of Diet On Gut Microbiome and Colorectal Cancer Developmentmentioning
confidence: 99%
“…Emulsifier consumption lowered the abundance of Clostridia (in both male and female mice) and increased the abundance of Proteobacteria (in male mice). Proteobacteria has been putatively linked to altered gut microbiome and risk for cancer ( 69 , 70 ). In another study, Viennois et al reported that CMC and polysorbate 80 induce low grade inflammation and alteration in the gut microbiota such as increase in Bacteroidales and decrease in Clostridiales ( 53 ).…”
Section: The Influence Of Diet On Gut Microbiome and Colorectal Cancer Developmentmentioning
confidence: 99%